Difabel, LSM dan Politik Intermediary: (Politik Advokasi LSM Sapda dalam menggoalkan Perda JAMKES Difabel Kota Yogyakarta) - Moh. Rafli Abbas; Reni Shintasari (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2016)
This study about the struggles of the NGO Sapda Yogyakarta in championing accessibility in policy making diffable clan. The behavior of the stigma against the disabled have long been reproduced by the Government and the community. Most people still consider diffable is a physical and mental ab- normalities that embarrass the family and should be covered. When disabled is the normal condition of a person with special needs because of physical limitations. Disabled is the symbol of the resis- tance and the representation of minority groups who often get discrimination.